Ellen Newbold La Motte collection on opium traffic - La Motte, Ellen Newbold, 1873-1961.; League of Nations. Advisory Committee on Traffic in Opium and Other Dangerous Drugs
Material relating to the League of Nations and the control of narcotic drugs. Includes mimeographed and printed matter originating from the proceedings of the League of Nations Advisory Committee on Traffic in Opium and Other Dangerous Drugs, reports of the committee to the League of Nations Council, minutes of the Council, and reports of league members.
Nurse, superintendent of the tuberculosis division of Baltimore (Md.) Health Department, traveler, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Drug control; Drug control -- International cooperation; Drug traffic; Drugs; Narcotics; Opium trade; League of Nations; League of Nations. -- Advisory Committee on Traffic in Opium and Other Dangerous Drugs; League of Nations. -- Council; Authors; Nurses